(3WQb GdbjGS GdGbJUGOjs - (3CehQj gGOj cGXe(B, (3GdMSfGhjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2002)
(3WHjYI GdbjGS GdGbJUGOj hGdfehPL GdNWj GdHSjW(B(SLM)(3,GdfehPL GdNWj GdYGe(B(GLM)(3,GdeQHYGJ GdUZQi GdYGeI heTcdI GdGQJHGW GdPGJj, GdeQHYGJ GdUZQi GdebjOI heTcdI GdJYOO GdNWj, efXheI GdeYGOdGJ GdBfjI, GdJfHDGJ, GdeQHYGJ GdUZQi GdehRhfI(B(WLS) (3heTcdI YOe GdJLGfSs
Keywords: (3GdGbJUGOs; (3GdbjGSs